2015
DOI: 10.1080/14693062.2015.1094726
|View full text |Cite
|
Sign up to set email alerts
|

Reformulating the low-carbon green growth strategy in China

Abstract: This synthesis article reviews China's efforts and effects concerning low-carbon green growth (LCGG) and explores the policy implications of reformulating the country's LCGG strategy. The article first reviews China's efforts in four major areas -carbon mitigation, market construction, fostering green industries, and managing the negative effects of LCGG -and then reviews China's LCGG effects with respect to the growth effect and the low-carbon effect. The results show that the increasingly stringent lowcarbon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 55 publications
(50 reference statements)
0
11
0
Order By: Relevance
“…It is notable that interest in green growth emerged following the global financial crisis of 2008-2009, with notable institutions such as the Organization for Economic Co-operation and Development (OECD) seeing the strategy as a twin economic and ecological solution (Girouard 2011;Borel-Saladin and Turok 2013;Ferguson 2015). Prior to emergence of the COVID-19 pandemic there was a growing perception that green growth was failing to deliver the required pace and scale of carbon-emissions reductions at national or international level (Zhang 2015).…”
Section: Discussionmentioning
confidence: 99%
“…It is notable that interest in green growth emerged following the global financial crisis of 2008-2009, with notable institutions such as the Organization for Economic Co-operation and Development (OECD) seeing the strategy as a twin economic and ecological solution (Girouard 2011;Borel-Saladin and Turok 2013;Ferguson 2015). Prior to emergence of the COVID-19 pandemic there was a growing perception that green growth was failing to deliver the required pace and scale of carbon-emissions reductions at national or international level (Zhang 2015).…”
Section: Discussionmentioning
confidence: 99%
“…For example, Tao et al [79] found that enterprises in Qingdao perceive low carbon strategies as unaffordable or a premature concept. However, Zhang et al [40] found that increasing LC policies has not reduced economic growth as anticipated. A study by Shen et al [12] in Beijing indicated that LCC has fostered green industries and brought impressive quality improvements, including structural change, and increased employment.…”
Section: Integrationmentioning
confidence: 93%
“…The lessons learned served as guides for subsequent pilot projects launched in 2012 (batch 2) and 2014 (batch 3; see Figure 1), [35,38] and allowed local governments to apply low carbon interventions into their planning and management models. Furthermore, the government has explored scientific approaches that undergird development in a sustainability realm [33], and national policies that advance China's utopian vision of an LCC [39,40]. These approaches and policies are disseminated in the 18th Chinese Congress declaration and report of ecological civilization (2012) [1,23,41], the 12th (2011-2015) and 13th (2016-2020) Five Years Plans (FYPs) [42], and the National New-type Urbanization Plan (2014-2020) [6].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Xiong et al (2017) compared the allowance mechanism of China's carbon trading pilots with alternative schemes in the EU and California. Zhang (2015) reformulated the low-carbon green growth strategy in China. considered emissions trading in China in terms of progress and future prospects.…”
Section: Brief Literature Discussionmentioning
confidence: 99%